E-AUDI: plataforma on-line de integração entre programas e estudantes de educação em áudio e empresas do setor de produção de conteúdo sonoro - Silva, Leandro Trajano da (2018)
Audio Education is a branch of formal training which focuses on professional audio, phonographic production, audio engineering, music technology etc. The literature review demonstrated that, although today's professional training can be considered the main way of entering in the professional field, there have been reports collected since the 1990s demonstrating that employers were concerned about the newly graduated trainees' lack of social skills. This work proposes that the solution for the problem is to invest in professional internship. Despite this tool may provide the student crucial contact to the "real world" of the field, other findings also demonstrated that only 21.42% of Brazilian audio education programs require professional internship in their school curriculum. Because of this, the researcher developed an online platform (E-AUDI / Audio Education at the Industry) to provide the so needed integration between audio education programs, their respective students and companies that produces sound related content. This platform will promote and facilitate communication between the three parts, thus stimulating the practice of professional internship and the consequent development of social working skills among the target students of the research. Indeed, it has been developed in a collaborative manner between the author and four other professionals in the areas of design, arts & medias and computer science. The final result points out that the functionality of the platform also depends on some factors, among them, the study of the causes of the lack of professional internship offering among the audio education programs in Brazil, a better understanding of the profile of the local audio industry, and the development of awareness about the importance of internship among its agents.